2010
DOI: 10.1186/1471-2202-11-32
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of peptidergic secretory granule transport are regulated by neuronal stimulation

Abstract: BackgroundPeptidergic neurons store and secrete the contents of large dense core vesicles (LDCVs) from axon terminals and from dendrites. Secretion of peptides requires a highly regulated exocytotic mechanism, plus coordinated synthesis and transport of LDCVs to their sites of release. Although these trafficking events are critical to function, little is known regarding the dynamic behavior of LDCVs and the mechanisms by which their transport is regulated. Sensory neurons also package opiate receptors in pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Electrical stimulation (ES) evokes vesicular release of glutamate (Glu) along DRG axons, at least in cocultures with oligodendrocytes (Wake et al, 2011 ). Observations demonstrating exocytosis of large dense core vesicles by chemically depolarized axons of trigeminal ganglion neurons further support the concept of activity-induced extrasynaptic axonal secretion (Sobota et al, 2010 ).…”
Section: Detection Of Axonal Activity By Scssupporting
confidence: 55%
“…Electrical stimulation (ES) evokes vesicular release of glutamate (Glu) along DRG axons, at least in cocultures with oligodendrocytes (Wake et al, 2011 ). Observations demonstrating exocytosis of large dense core vesicles by chemically depolarized axons of trigeminal ganglion neurons further support the concept of activity-induced extrasynaptic axonal secretion (Sobota et al, 2010 ).…”
Section: Detection Of Axonal Activity By Scssupporting
confidence: 55%
“…Interestingly, large DCV transport in axons has been shown to be activity-dependent. Stimulation of cultured trigeminal neurons with KCl (to depolarize them) increased the fraction of DCVs moving in an anterograde direction, though it also decreased their instantaneous velocity (Sobota et al 2010). Additional studies will be necessary to determine whether estradiol regulates the factors that control DCV maturation and/or their movements within axons.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further investigate this effect during early development, we used early life MS, which has been commonly used to study G × E interaction on anxiety and depression in mice 50 , 51 and has been shown to impact anxiety-like behaviors in rodents via the 5-HT system 52 , 53 . Exposure of wildtype mice, on a mixed c57BL6/J–129S6/Sv background, to MS significantly decreased distance travelled and time spent in the center of the OFT, while MS had no effect in Tph2 KI mice 54 .…”
Section: Discussionmentioning
confidence: 99%